Pleural Fluid suPAR Levels Predict the Need for Invasive Management in Parapneumonic Effusions - Arnold, David T. (Am J Respir Crit Care Med, 2020)
Rationale: Parapneumonic effusions have a wide clinical spectrum. The majority settle with conservative management but some progress to complex collections requiring intervention. For decades, physicians have relied on pleural fluid pH to determine the need for chest tube drainage despite a lack of prospective validation and no ability to predict the requirement for fibrinolytics or thoracic surgery. Objectives: To study the ability of suPAR (soluble urokinase plasminogen activator receptor), a potential biomarker of pleural fluid loculation, to predict the need for invasive management compared with conventional fluid biomarkers (pH, glucose, and lactate dehydrogenase) in parapneumonic effusions. Methods: Patients presenting with pleural effusions were prospectively recruited to an observational study with biological samples stored at presentation. Pleural fluid and serum suPAR levels were measured using the suPARnostic double-monoclonal antibody sandwich ELISA on 93 patients with parapneumonic effusions and 47 control subjects (benign and malignant effusions). Measurements and Main Results: Pleural suPAR levels were significantly higher in effusions that were loculated versus nonloculated parapneumonic effusions (median, 132 ng/ml vs. 22 ng/ml; P < 0.001). Pleural suPAR could more accurately predict the subsequent insertion of a chest tube with an area under the curve (AUC) of 0.93 (95% confidence interval, 0.89–0.98) compared with pleural pH (AUC 0.82; 95% confidence interval, 0.73–0.90). suPAR was superior to the combination of conventional pleural biomarkers (pH, glucose, and lactate dehydrogenase) when predicting the referral for intrapleural fibrinolysis or thoracic surgery (AUC 0.92 vs. 0.76). Conclusions: Raised pleural suPAR was predictive of patients receiving more invasive management of parapneumonic effusions and added value to conventional biomarkers. These results need validation in a prospective multicenter trial.